2022
DOI: 10.1088/1674-4527/ac9579
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the Farthest Globular Cluster NGC 6715 and Two Other GCs in Gamma-Rays with Fermi-LAT

Abstract: In this paper, $\sim12-$year long$-$term Pass 8 data from \emph{Fermi} Large Area Telescope for the 157 globular clusters are carefully re-analyzed. Besides the 31 globular clusters reported in the fourth \emph{Fermi} Large Area Telescope catalogue Data Release 2, NGC 1851 is identified as a gamma-ray emitter and the significant gamma$-$ray emissions from NGC 6715 and NGC 6723 are detected. Especially NGC 6715 locates at a distance of 26.8 kpc, so far it is the farthest globular cluster detected in gamma-rays.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…It can be seen that there is one MSP, PSR J1312 +1810E, in NGC 5024 with  E> 10 35 erg s −1 . No emission has been found from this GC (e.g., Yuan et al 2022a), while it can be noted that the distance to the GC is large, ∼18 kpc (Harris 1996;Baumgardt & Vasiliev 2021), which may explain the nondetection at γ-rays of the GC (or the MSP). In any case, this MSP is of interest as its η already reaches ∼10 −3 .…”
Section: Implication For γ-Ray Emissions Of Gc Mspsmentioning
confidence: 88%
“…It can be seen that there is one MSP, PSR J1312 +1810E, in NGC 5024 with  E> 10 35 erg s −1 . No emission has been found from this GC (e.g., Yuan et al 2022a), while it can be noted that the distance to the GC is large, ∼18 kpc (Harris 1996;Baumgardt & Vasiliev 2021), which may explain the nondetection at γ-rays of the GC (or the MSP). In any case, this MSP is of interest as its η already reaches ∼10 −3 .…”
Section: Implication For γ-Ray Emissions Of Gc Mspsmentioning
confidence: 88%
“…It can be seen that there is one MSP, PSR J1312+1810E, in NGC 5024 with Ė >10 35 erg s −1 . No emission has been found from this GC (e.g., Yuan et al 2022a), while it can be noted that the distance to the GC is large, ∼18 kpc (Harris 1996;Baumgardt & Vasiliev 2021), which may explain the non-detection at γ-rays of the GC (or the MSP). In any case, this MSP is of interest as its η already reaches ∼ 10 −3 .…”
Section: Implication For γ-Ray Emissions Of Gc Mspsmentioning
confidence: 86%
“…Dedicated pulsar searches in the radio band, as well as searches for gamma-ray pulsations, could shed significant light on the nature of the Sgr/M54 system. Recently, Yuan et al (2022) performed a study of a number of gamma-ray bright GCs, including M54. The authors searched for pulsations in Fermi-LAT data and found no evidence for time-dependent variations in M54's flux.…”
Section: Dark Matter Interpretationmentioning
confidence: 99%